Global, regional, and national burden of chronic respiratory diseases,1990–2021 and predictions to 2035: analysis of data from the global burden of disease study 2021 - Ying Zhai; Chuanmiao Zhu; Tengxiao Zhu; Wenjing Song; Yu Tang; Luqing Jiang; Fengxia Ruan; Zichen Xu; Lei Li; Xia Fu; Daoqin Liu; Aidong Chen; et al. (Annals of Medicine)
Background Chronic respiratory diseases (CRDs) have undergone significant epidemiological shifts in recent decades. This study comprehensively analyses the evolving global and regional burden of CRDs over the past 30 years and their attributable risk factors, aiming to identify key trends and inform effective prevention and control strategies.Methods Using data from the Global Burden of Disease (GBD) 2021 database, this study examines trends in age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life years rate (ASDR) for CRDs from 1990 to 2021, across global, regional, and national levels. Estimated annual percentage change (EAPC) was employed to quantify ASR trends over specified intervals. Additionally, Bayesian age-period-cohort (BAPC) modeling was utilized to depict and project CRD trends through 2035.Results In 2021, the global incidence of CRDs was 55.21 million (95% UI 48.68–64.56), predominantly comprising asthma (37.86 million; 95% UI 31.38–46.92) and chronic obstructive pulmonary disease (COPD) (16.90 million; 95% UI 15.47–18.34),  followed by interstitial lung disease (ILD) and pulmonary sarcoidosis (0.39 million; 95% UI 0.35–0.43) and pneumoconiosis (0.06 million; 95% UI 0.05–0.07). Since 1990, the age-standardized prevalence (ASPR) of CRDs has generally declined, except for ILD and pulmonary sarcoidosis, which increased by 8.74%. The global ASIR of CRDs is projected to continue declining, reaching 517.25 per 100,000 population by 2035, with ASMR of 39.21 per 100,000. Risk factor studies have shown that solid fuels burden remained higher among females in low-middle sociodemographic index (SDI) areas, while smoking-attributable burden predominated among males.Conclusion This study characterizes the CRD burden across regions, ages, and sexes, identifying key risk factors to inform burden–reduction policies.